Use of a real-time PCR method to quantify the primary infection of Plasmopara viticola in commercial vineyards - Lujia Yang; Bingyao Chu; Jie Deng; Kai Yuan; Qiuyu Sun; Caige Jiang; Zhanhong Ma (Phytopathology Research, 2023)
Abstract Grapevine downy mildew (GDM) caused by Plasmopara viticola is a recurrent disease of wine grapes in the Ningxia Hui Autonomous Region (Ningxia) of northwestern China. However, the primary infectious pathogen in this region has not been thoroughly investigated. In this study, a multiplex real-time PCR assay was utilized to quantify P. viticola in soil, leaf residues, and asymptomatic leaf samples from ten commercial vineyards in two consecutive years to better understand the epidemiological significance of overwintering primary inoculum and its inoculum potential before the appearance of the first visual GDM symptoms. The DNA primers and multiplex real-time PCR assays that had been established exhibited specificity towards P. viticola within the test samples. The majority of the asymptomatic leaves (60%), leaf residues (80%), and soil samples (100%) tested positive for P. viticola. In addition, the amount of primary inoculum of P. viticola was found to be lower in soil than in leaf residues. The area under the disease progress curve in terms of the molecular disease index (AUDPC-MDI) was used to evaluate the overall latent P. viticola infection in asymptomatic leaves. Asymptomatic leaves were found to have different levels of P. viticola infection, and high AUDPC-MDIs correlated with a high AUDPC in terms of disease index (AUDPC-DI), with a significant correlation relationship between them (P < 0.01). Additionally, a well-correlated relationship was observed between the disease progress in the previous year and the MDIs of leaf residues and asymptomatic leaves in the following year, as well as the AUDPC-DI (Spearman’s correlation coefficient ρ = 0.643, 0.498, and 0.595, respectively) (P < 0.01). These findings provide valuable information for quantifying the primary infection of P. viticola in commercial vineyards.